Roles of Deletion of Arid1a, a Tumor Suppressor, in Mouse Ovarian Tumorigenesis - Guan, Bin (Oxford University Press, 2014)
The chromatin remodeling gene, ARID1A, has been implied as a tumor suppressor, and its somatic inactivating mutations occur in a wide variety of human cancers, most frequently in ovarian and uterine endometrioid and ovarian clear cell carcinomas. Tumors with ARID1A mutations also frequently harbor PTEN or PIK3CA mutations, suggesting their collaboration in tumorigenesis. Here, we used a conditional knockout mouse model in which Arid1a and Pten were deleted either individually or in combination in the mouse ovarian surface epithelium. After 6 months, 59.1% of mice with Arid1a and Pten double knockout developed ovarian endometrioid or undifferentiated carcinoma, whereas the remaining mice showed hyperplasia of ovarian surface epithelium. In contrast, 52 mice with homozygous or heterozygous deletion in either Arid1a or Pten did not develop ovarian lesions. These results demonstrate that inactivation of Arid1a alone is insufficient for tumor initiation but it requires additional genetic alteration(s) such as Pten deletion to drive tumorigenesis.